Socialist People's Libyan Arab Jamahiriya : 2008 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Socialist People's Libyan Arab Jamahiriya. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Socialist People's Libyan Arab Jamahiriya's 2008 Article IV Consultation is focused on containing public expenditure to reduce inflation pressures, strengthening the monetary policy framework, and advancing financial sector reforms. Libya's macroeconomic performance has been strong. GDP growth is broad-based and has strengthened further. Both the fiscal and external current account positions are in large surplus, and net foreign assets are accumulating rapidly. The medium-term outlook is favorable, underpinned by the expectation of high oil prices and increased infrastructure spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet